2020
DOI: 10.1016/j.heliyon.2019.e03133
|View full text |Cite
|
Sign up to set email alerts
|

Structural, vibrational and optical studies on semiorganic crystals of boric acid potassium acetate

Abstract: A semiorganic crystal of Boricacid potassium acetate has been grown by low temperature solution growth technique at room temperature using deionized water as a solvent. The crystalline nature of the compound was confirmed by the sharp and well defined peaks observed from the powder X-ray diffraction pattern. By single crystal X-ray diffraction method, the structure of the grown crystal has been studied. The Boric acid Potassium Acetate (BAPA) crystal has good optical transmittance in the entire UV visible regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…24,26 The B–O, B–OH, and O–B–O stretching peaks are observed around 1640, 1300 and 1100, and 670 cm −1 for the prepared boron precursor sample. 28,29,38,39…”
Section: Resultsmentioning
confidence: 99%
“…24,26 The B–O, B–OH, and O–B–O stretching peaks are observed around 1640, 1300 and 1100, and 670 cm −1 for the prepared boron precursor sample. 28,29,38,39…”
Section: Resultsmentioning
confidence: 99%
“…Let G be a BAG(p, q). Then the P I-polynomial of BAG(p, q) is generalized as follows, 2 [y e−4q+1 (4q − 4qy 4 + y 4q − 3y 4 + 3y 4q+4 − 1) + (4q + 2)(y e−4q−2 )(y 4 − 1) 2 − (4q + 4)y e−4q−4 (q − p + 1)(y 4 − 1) 2 + 2y e−4q−1 (4q − 4qy 4 − y 4q − 5y 4 + 5y 4q+4 + 1) + (y 4 − 1) 2 ((4q + 4)y e−4q−4 (p − q) + (2p + 1)y e−2q−1 + (2p − 1)(2q + 2)y e−2q−2 + + (4p + 2q + 2)y e−1 + 2qy e−1 − (q − p)y e−1 + 2y e−1 (q − 1) + y e−1 (p − q + 1) + 2py e−1 )].…”
Section: 3(b)unclassified
“…However there are possible drawbacks in terms of solubility and hydrolysis reactions and the current standard of care is to use boric acid exclusively. The use of boric acid has the advantages of being sufficiently soluble in water to yield the required concentrations having sufficient chemical and physical stability over the required temperature range and having a low proclivity for incorporation into oxide films which could result in local neutron poison and acidity [1] established the equilibrium constants and showed that the initial reaction of H 3 BO 3 was the key predictor of pH in the primary coolant in a study of boric acid dissociation over temperatures relevant to a PWR [2]. This is because polyborates lose their relevance at high temperatures, low boron concentrations and low hydroxide concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many borate crystal series such as potassium boro succinate, strontium boron beryllium oxide, dipotassium boro maleate, and cesium lithium triborate are synthesized and analyzed for their nonlinear properties. [ 8 ] Alkali hydrogen phthalates such as potassium acid phthalate (KAP), sodium acid phthalate (NaAP), and lithium acid phthalate (LiAP) have been studied for their electronic, optoelectronic, and electroacoustic applications. [ 9,10 ] Following a similar pattern, a semiorganic crystal combining the nonlinear capabilities of boric acid and phthalic acid, nickel boro phthalate (NBP), has been investigated for its nonlinear optical properties.…”
Section: Introductionmentioning
confidence: 99%